Adolescent Peers and Prevention: Network Patterns of Sexual Violence Attitudes and Bystander Actions. Issue 13 (July 2022) - Banyard, Victoria; A. Waterman, Emily; M. Edwards, Katie; Valente, Thomas W.
Peer sexual violence is a significant social problem that affects adolescents and can lead to negative mental health and developmental consequences. Peers are a significant source of influence for adolescent behavior. For example, recent studies show training teens to be bystanders can be an effective prevention strategy to reduce peer violence and harassment. Peers can also promote risky behaviors including substance use and violence. The current study examined how sexual violence-specific risk and protective attitudes (e.g., denial of peer sexual violence and positive peer prevention norms) and behaviors (alcohol use and bystander actions to prevent peer sexual violence) clustered within peer networks cross-sectionally and over time. Participants were 1, 499 7th−10th graders who took surveys during an academic year and who reported having opportunity to take action as bystanders to peer sexual violence. Participants took surveys 6 months apart online in schools. Questions included nomination of best friends to capture information about peer networks. Social network analyses indicated that there was weak but significant clustering of positive prevention attitudes such as bystander denial and marginal clustering on reactive bystander behaviors to address sexual assault. For comparison, alcohol use and academic grades were analyzed and found to also cluster in networks in these data. These findings suggest that for early adolescents, peer bystander training may be influential for some key bystander attitudes and reactive sexual violence prevention behaviors as individual behaviors are not independent of those of their friends.